Bit Error Rate Analysis of MC-CDMA Systems with Channel Identification Using Higher Order Cumulants - Mohammed Zidane; Said Safi; Mohamed Sabri; Ahmed Boumezzough (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
The aim of this paper is to contribute to study the problems of the blind identification and equalization using Higher Order Cumulants (HOC) in downlink Multi-Carrier Code Division Multiple Access (MC-CDMA) systems. For this problem, two blind algorithms based on HOC for Broadband Radio Access Network (BRAN) channel are proposed. In the one hand, to assess the performance of these approaches to identify the parameters of non minimum phase channels, we have considered two theoretical channels, and one practical frequency selective fading channel called BRAN C, driven by non gaussian signal. In the other hand, we use the Minimum Mean Square Error (MMSE) equalizer technique after the channel identification to correct the channel distortion. Theoretical analysis and numerical simulation results, in noisy environment and for different signal to noise ratio (SNR), are presented to illustrate the performance of the proposed methods.